Synthesis and herbicidal activity of new pyrazole ketone derivatives. (6th October 2020) - Fu, Qing; Kang, Sheng-Jie; Zhong, Liang-Kun; Chen, Jie; Tan, Cheng-Xia; Weng, Jian-Quan; Xu, Tian-Ming; Liu, Xing-Hai
Abstract: A series of pyrazole derivatives was designed according to prodrug strategy. These compounds were synthesized via eight steps and their structures were confirmed by 1 H NMR spectroscopy and MS. The preliminary herbicidal bioassay results indicated that the title pyrazole ketone compounds exhibited low herbicidal activity against six weeds at 150 g/ha, which is weaker than that of the commercial HPPD herbicide topramezone. The docking results showed that the binding mode of the key intermediate (3-(2-(2-fluorophenoxy)ethoxy)-2-methyl-4-(methylsulfonyl)phenyl)(5-hydroxy-1, 3-dimethyl-1H-pyrazol-4-yl)methanone is the same as the reported inhibitor DAS689 in the complex. Graphical Abstract: